Role Play Learning-Based Indonesian Language Instruction as a Strategy to Enhance Speaking Skills - I Nyoman Surata; I Nyoman Ari Wira Saputra; Ni Wayan Ari Kusuma Dewi; I Putu Arya Wardiana; ⁠I Nyoman Sudiana; Ida Bagus Putra Yasa (International Journal of Language and Literature, 2025)
Currently, students' speaking skills are still relatively low, characterized by a lack of courage to express opinions, limited vocabulary, and minimal participation in discussions. Indonesian language learning still relies on the lecture method, resulting in students being passive and less engaged. Therefore, learning innovation is needed. Therefore, this study aims to analyze the effectiveness of Role Play Learning in improving Indonesian language speaking skills. The method used is a One-Shot case study with 30 students from class VI B as research subjects. The research instruments were a linguist-validated speaking skills test and observations of the learning process. The test data were analyzed descriptively and quantitatively using SPSS software version 25, with a focus on changes in speaking skill scores before and after the implementation of the Role Play Learning method. The results of the study showed a significant increase in students' speaking skills, with an average score increasing from 65.40 in pre-learning to 81.75 in post-learning. In addition, this increase was supported by teacher observations of students' attitudes, courage, and verbal interactions during the learning process. The implementation of Role Play Learning has been proven effective in creating an active, enjoyable learning atmosphere and encouraging maximum student participation.